2016
DOI: 10.5539/ies.v9n10p245
|View full text |Cite
|
Sign up to set email alerts
|

School Principals’ Authentic Leadership and Teachers’ Psychological Capital: Teachers’ Perspectives

Abstract: This study examined teachers' perceptions of principals' authentic leadership and the relationship of authentic leadership to teachers' psychological capital in Taiwan. A total of 1,429 elementary and secondary school teachers were surveyed. The results showed that teachers perceived their principals' authentic leadership as moderate and that the principals' practice of authentic leadership was influenced by culture. Moreover, the principals' authentic leadership was found to be positively and significantly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 32 publications
0
26
0
10
Order By: Relevance
“…The followers of authentic leaders compared with other leadership styles followers experience more positive emotional states through emotional contagion from leader to them (Rego, Sousa, Marques, & Cunha 2012). Several studies indicate that there is a positive and significant relationship between authentic leadership and psychological capital (Clapp- Smith, Vogelgesang, & Avey, 2009;Feng-I, 2016;Jensen & Luthans, 2006;Munyaka, et al, 2017;Peterson, Walumbwa, Avolio, & Hannah, 2012;Rego et al, 2012;Walumbwa et al, 2011;Woolley, Caza, & Levy, 2010). According to the above, the second hypothesis of this study could be as following:…”
Section: Authentic Leadership and Psychological Capitalmentioning
confidence: 68%
“…The followers of authentic leaders compared with other leadership styles followers experience more positive emotional states through emotional contagion from leader to them (Rego, Sousa, Marques, & Cunha 2012). Several studies indicate that there is a positive and significant relationship between authentic leadership and psychological capital (Clapp- Smith, Vogelgesang, & Avey, 2009;Feng-I, 2016;Jensen & Luthans, 2006;Munyaka, et al, 2017;Peterson, Walumbwa, Avolio, & Hannah, 2012;Rego et al, 2012;Walumbwa et al, 2011;Woolley, Caza, & Levy, 2010). According to the above, the second hypothesis of this study could be as following:…”
Section: Authentic Leadership and Psychological Capitalmentioning
confidence: 68%
“…The education problems faced by the younger generation include a decrease in the number of students enrolled and a surplus of teachers [ 52 ]. As a result of the low birthrate, primary schools have reported that the wave of decline has affected heavily [ 48 ], and with the instability of the retirement system resulting from previously announced adjusted pension policies, the older group of school teachers retired several years ago [ 53 ]. Therefore, the faculty in primary schools represents a younger population, and more teachers are available than are required; this has resulted in a wide range of “stray” teachers, and those with a teaching license are yet unable to obtain a formal position due to a lack of vacancies [ 52 ].…”
Section: Related Workmentioning
confidence: 99%
“…Tras analizar los estudios incluidos en la revisión se puede establecer que son escasos los estudios que analizan los predictores (o antecedentes) del capital psicológico entre el profesorado (ver Figura 3). No obstante, se advierte que el liderazgo auténtico del personal de dirección, caracterizado por la autoconciencia, la transparencia relacional, la perspectiva moral internalizada y el procesamiento equilibrado, predice el capital psicológico del profesorado universitario, de Primaria y de Secundaria (Adil y Kamal, en prensa; Feng, 2016). Del mismo modo, el apoyo social y el apoyo organizacional percibido podrían considerarse protectores del capital psicológico, ya que el profesorado que se siente apoyado en su trabajo presenta mayor capital psicológico (Kanapathy, 2016;Li et al, 2019;Li y Zhang, 2019).…”
Section: Factores Que Predicen El Capital Psicológicounclassified